Analytical and Numerical Modeling of Impact Loading Cantilever Sandwich Beam with Aluminum Foam Core and Steel Facesheets - Mohammad Solooki (مجله مدل سازی در مهندسی)
Due to having advantages such as high strength, lightness, and crack-resistant properties, sandwich structures are widely used in aircraft, missile, marine, and medical industries. For this purpose, in this research, the analytical and numerical investigation of low velocity impact on cantilever sandwich beams with foam core and metal facesheets has been done. In the analytical part, using the GALERKIN method, the equations governing the rise were calculated and the speed and acceleration equations of the sandwich beam were extracted. ABAQUS software has also been used to simulate this process. Finally, the effects of parameters such as impact load application location, core density and strength, projectile mass and velocity, and dimensions have been analyzed and compared analytically and numerically on the deflection of the sandwich beam. By examining and comparing the obtained results, it was observed that, firstly, there is a good agreement between the analytical and numerical results, and secondly, with the movement of the place of application of the load from the free support to the cantilever support of the beam, the final shape of the upper part of the sandwich changes. The beam is reduced by 9.6% and by increasing the rate of projectile mass from 0.01 to 0.04 and reducing the projectile width from 0.05 to 0.01, the final rise of the upper surface increases by 71% and 44%, respectively.